1516 Electrophysiological Study of Peripheral Nerves in Children with Acute Lymphoblastic Leukemia. (October 2012) - Imam, M
Abstract : Introduction: Acute lymphoblastic leukemia (ALL) is a malignant disorder of lymphoid progenitor cells, affects both children and adults. Chemotherapy induced peripheral neurotoxicity is an important side-effect of several chemotherapeutic agents. The Aim: of study was to detect the presence and types of peripheral neuropathy in newly diagnosed children with acute lymphoblastic leukemia, before and after the phase of induction of remission. Patients and Methods: 24 patients newly diagnosed as ALL were enrolled into the present study (group I); they were subjected to clinical and electrophysiological assessments which assess the integrity of the peripheral nervous system through conducting nerve conduction study and electromyography before and after receiving the chemotherapeutic agents. Ten apparently healthy children served as controls (group II). Results: 16 cases (67%) out of the 24 examined ALL patients were proved electrophysiologically to be free from PN, while 8 cases (33%) were found to have PN and they were distributed as follows: 2 patients (8.3%) were proved to have chemotherapy induced PN, 4 patients (16.6%) showed subclinical chemotherapy induced PN and 2 patients (8.3%) showed subclinical PN due to ALL itself. 5 cases (62.5%) were found to have axonal pattern of PN, 1 case (12.5%) was found to have demyelinating pattern of PN and 2 cases (25%) were found to have mixed axonal demyelinating pattern of affection. Motor nerves affection was greater than sensory nerve. Conclusion: Chemotherapeutic agents used in phase I (induction of remission) proved to have a neurotoxic effects on peripheral nerves. In most of the patients, the peripheral neuropathy was subclinical.